Analysis of the chloramphenicol resistance determinant of plasmid R26 - Dorman, Charles James (Trinity College (Dublin, Ireland). Department of Microbiology, 1985)
The Inc P-1 plasmid, R2B carries an inducible chloramphenicol resistance determinant, cml. This specifies low level chloramphenicol resistance (30 μg/ml] in Escherichia coli. The mechanism does not involve drug detoxification or ribosomal modification, but may involve a permeability barrier to drug uptake acting at the cytoplasmic membrane. Experiments described in this thesis show that cml also specifies resistance to some fluorinated derivatives of chloramphenicol.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin